Motif Dan Kepuasan Menonton Tayangan Televisi Studi Korelasi Motif Dan Kepuasan Dalam Menonton Tayangan Indonesia Lawak Klub Di Trans7 Pada Kalangan Mahasiswa Hukum Universitas Muhammadiyah Surakarta Angkatan 2013 - Wibowo, Nia Afifah, Agus Triyono, M.Si, Budi Santoso, S.Sos, M.Si (2016)
The Existence of the mass media is very popular and loved by the general public especially the mass media television. In late, flourishing comedy impressions appear on various television stations, researches interested in researching a television comedy genre in particular impressions Indonesia Lawak Klub. So, researcher wants to know the level of the gap between motive and satisfaction Indonesia Lawak Klub audience impressions, especially in the Faculty of Law, University of Muhammdiyah Surakarta, class of 2013. This research is quantitative research with correlation approach. As the sampling technique using random sampling. Data collection technique using questionnaires and data analysis techniques using the technique of discrepancy gap analysis. The findings of study: 1). The level of the gap between the motive and the Law UMS students satisfaction in watching Indonesia Lawak Club Trans7 seen from the aspect of information including in the medium category with a value gap by 13%, 2). Rate gap between seen from the aspect of personal identity included in the low category with value gap by 21%, 3). Rate gap between seen from the aspect of integration and social interaction are included in the high category with a value gap of 7%, 4). Rate gap between seen from the aspect of entertainment is included in the low category with a value gap of 42%.